The Effectiveness of Hybrid Learning Model with Emotional Design Approach in Improving Digital Literacy of Junior High School Students - Fatmasari, Ria Kristia (Journal of English Language and Education, 2025)
Digital transformation in education demands a learning model that is not only technically effective but also pays attention to students' emotional involvement. Digital literacy is an important competency that must be possessed by students since junior high school age, but its implementation still faces challenges in terms of student motivation and participation. This study aims to examine the effectiveness of the hybrid learning model with an emotional design approach in improving digital literacy of junior high school students. The method used is a quasi-experiment with a pretest-posttest control group design. The study population was grade VIII junior high school students at a school in North Sumatra. The research instruments consisted of digital literacy tests, observations of emotional involvement, and documentation of learning activities. Data were analyzed quantitatively and qualitatively. The results showed a significant increase in digital literacy in the experimental group compared to the control group. The average posttest increased by 22.17 points . Observations showed that students were more active and emotionally involved in learning. The hybrid learning model with an emotional design approach has been proven to be effective in improving digital literacy and student involvement in digital learning. This approach can be an innovative alternative in 21st century learning.